Syndrome in Question - Guida Santos; Lourdes Sousa (Sociedade Brasileira de Dermatologia, 2014)
Multiple autoimmune syndrome is a rare condition, described by Humbert and Dupond in 1988. It is defined by the association of at least 3 autoimmune diseases in the same patient. Vitiligo is the most common skin condition in this syndrome. This article presents the case of a 31-year-old male with vitiligo, alopecia areata, Crohn's disease, psoriasis vulgaris and oral lichen planus. The rarity of this case is highlighted by the coexistence of four autoimmune skin diseases in association with Crohn's disease, never described in the literature.